A systematic review on comparison of periapical healing and post-operative pain between bioceramic and epoxy resin based sealers - Deepali Mahajan; Devansh Manocha; Priyesha Patel; Maulik B Saraiya; Keral Chaniyara (Wolters Kluwer Medknow Publications, 2023)
To compare the incidence of postoperative discomfort and periapical healing in endodontically treated teeth following the use of resin-based or bioceramic sealers. In vivo, clinical trials were included in the study. The selection criteria, data extraction, and analysis were performed to evaluate the quality and publication bias of the selected studies. The primary outcome measure was the comparison of postoperative discomfort between the two sealer types. Seven studies were included in the systematic review, with a modest level of evidence found in the quality assessment. There are no significant differences in the postoperative discomfort levels between resin-based and bioceramic sealers. However, the overall quality of the clinical trials was moderate, highlighting the need for further well-designed clinical trials with appropriate measures of randomization, allocation concealment, and blinding to establish a definitive conclusion on the incidence of Postoperative discomfort associated with the use of these sealers.